Graphics calculators integration into curriculum (1998)
The effects of graphic calculators on the teaching and learning of mathematics depend on how this new technology is integrated into the curriculum. Current research shows that graphic calculators can enhance the learning of functions and graphing concepts and the development of spatial visualization skills (Penglase and Arnold, 1996). However, most studies do not give detailed information on the way the calculators were integrated into the curriculum. Three main integration phases are proposed: introduction, adaptation and consolidation. Each phase is characterized by the way the calculators are used by the students and the teacher, by the type of tasks that are done by them or proposed by the textbook and by the role played by graphic calculators in assessment. These integration phases depend strongly on how mathematical knowledge is seen by the different pedagogical agents and on the visions that the institution, the teacher and the textbook have on teaching, on learning and on the role of the graphic calculator in those processes. Results from a study presented here show the importance of taking into account these integration phases. An analysis is made on the way mathematical knowledge can be approached depending on how the technology is integrated into the curriculum.